2022
DOI: 10.9755/ejfa.2022.v34.i4.2851
|View full text |Cite
|
Sign up to set email alerts
|

Physicochemical and bioactive characterization of beekeeper and market honeys

Abstract: Honey is a popular sweetener that makes significant contributions to human nutrition. The aim of this study was to analyze and comparespecific properties relating to honey quality and biological value such as total phenolic content, color, color intensity, proline and otherquality parameters like moisture content, electrical conductivity, 5-hydroxymethylfurfural, diastase activity in various honeys directly frombeekeepers and from markets. In total fiftysix honey samples directly from Czech and Slovak beekeepe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 25 publications
1
1
0
Order By: Relevance
“…The diastase index showed small variation between the honey samples. According to a research of Tkáè et al [22], longan flower honey from 3 regions Poland, Italy and Turkey had a diastase index of 22.6 Shades, 21.8 Shades and 16.6 Shades, respectively [22]. Comparing the above results with three samples of honey in this study, it could be observed that the and Cai Be (CB) districts of Vietnam diastase index of Tan Phu Dong and Cai Be honey was much lower.…”
Section: Resultssupporting
confidence: 55%
“…The diastase index showed small variation between the honey samples. According to a research of Tkáè et al [22], longan flower honey from 3 regions Poland, Italy and Turkey had a diastase index of 22.6 Shades, 21.8 Shades and 16.6 Shades, respectively [22]. Comparing the above results with three samples of honey in this study, it could be observed that the and Cai Be (CB) districts of Vietnam diastase index of Tan Phu Dong and Cai Be honey was much lower.…”
Section: Resultssupporting
confidence: 55%
“…Trigona honey is assessed to have a yellow-red hue value of 53.50 and a brightness level of 6.61±0.48 (Moniruzzaman et al, 2014). Pollen sources, sugar constituents, antioxidants like carotenoids, xanthophylls, and cyan pigments, minerals, amino acids, and phenolic substances (primarily flavonoids), and 5-HMF which is produced by honey heating or prolonged storage via the Maillard reaction, all contribute to substantial changes in honey color (Shamsudin et al, 2019;Tkáč et al, 2022). The color of the honey, however, does not vary with the bee species (Nordin et al, 2018;Avila et al, 2019a).…”
Section: Color and Viscositymentioning
confidence: 99%
“…The parameter used for measuring the aging of honey is HMF concentration, which is the most significant intermediate product of two reactions: degradation of hexose and decomposition of 3-deoxyosone in the Maillard reaction (Salis et al 2021). The color depends on several factors, although it is primarily related to the botanical origin and composition of the nectar, collection process, temperature, and storage time (Tkáč et al 2022). Water activity (a w ) is a significant factor in preventing or restricting microbial growth and, in many cases, is the key parameter responsible for the stability of food, modulation of the microbial response, and determination of the type of microorganisms found in foods (Ikhsan et al 2022).…”
Section: Introductionmentioning
confidence: 99%